EFFECT OF CITRAL ON NONALCOHOLIC STEATOHEPATITIS (NASH) VIA AMPK-MEDIATED AUTOPHAGY AND INFLAMMASOME PATHWAY IN TYPE 2 DIABETIC MICE - Mishra, Chetna; Tripathi, Dinesh; Tiwari, Sunita; Verma, Narsingh (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Nonalcoholic steatohepatitis (NASH) is the progressive form of non-alcoholic fatty liver disease (NAFLD), associated with lipotoxicity-induced autophagy defects and significantly increased inflammasome expression. Citral, a terpenoid and the main constituent of Lemongrass, is reported to have multiple biological activities. This study aimed to investigate the effect of citral on mechanisms underlying the relationship between the autophagy Inflammatory and lipid metabolism-related gene deregulation associated with NASH using an in vivo model of type 2 diabetes. METHODOLOGY Thirty male BALB/c mice were randomly divided into three groups: control (n = 10), model (n = 10), and treatment (citral) group (n = 10). Mouse models of NAFLD and diabetes were established using a high-fat diet and streptozocin. RESULTS The levels of fasting blood glucose (FBG), total cholesterol (TC), and triglyceride (TG) in the serum were significantly reduced after citral treatment. The levels of insulin, leptin and adiponectin were also corrected by citral treatment. Treatment with citral markedly reduced the levels of liver injury markers, malondialdehyde (MDA), alanine aminotransferase (ALT) and Aspartate transaminase (AST) and inflammatory markers like TNF-α and Caspase 3 and CRP levels. The expression of AMPK, LC3-II, Beclin-1 and Parkin were increased significantly, whereas mTor, ACC and NLRP3 and IL-1β proteins were suppressed after citral treatment. CONCLUSION These results suggest that citral stimulates activity of AMPK and inhibit the NLRP3 inflammasome by enhancing the autophagy pathway in liver, which makes it a promising candidate for a therapeutic agent for the management of NASH associated with diabetes.